Towards innovative models of management in public administration: The case of Chile’s Public Postal Service - Villanueva, Susana (Estado, Gobierno y Gestión Pública, 2012)
Innovation has become increasingly relevant in the last years, as a framework for the implementation of quality management models suited to the nature of public organizations, which generate value. This article examines the case of Chile’s Public Postal Service, analyzing its management modelin light of the principal quality management models. The analysis focuses on five variables, through which the main elements of the Postal Service’s quality management system are identified.